S. Cowling. Kantian Humility and Ontological Categories / trans. from Engl. A. V. Nekhaev - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность")
Kant has a distinction between things in themselves and phenomena. Things as we know them consist ‘wholly of relations’ therefore we have no insight into ‘the inner’ of things. Kant says that we have no knowledge of the intrinsic properties of things. There are irremediable constraints on what we can know, inevitable limits on what we can become acquainted with. This is a kind of Epistemic Humility. It entails Categorical Humility, according to which we are just as irremediably ignorant of the categorical properties of entities. Ignorance of the categorical structure of the world creates two problems for defenders of Kantian Humility. First, if we know that Kantian Humility to be true, it must be false. Second, if Kantian Humility is true, the argument for it cannot succeed.